STRATEGI PEMASARAN PRODUK COKELAT KELOR - Ndaong, Sonya Santika Swastri; Nikolaus, Serman; Bernadina, Lika (Undana Press, 2024)
This research was carried out at the Alfa Omega Tarus Fondation, Central Kupang District, Kupang Regency from June to July 2023. This research was conducted with the aim of (1) to determine the characteristics of Moringa chocolate products at the Alfa Omega Tarus Foundation, Central Kupang District, Kupang Regency, (2) knowing the marketing strategy for Moringa chocolate implemented at the Alfa Omega Tarus Foundation, (3) knowing how the Moringa chocolate production process works. This research used four methods, namely observation, interviews, documentation and questionnaires with a total of 20 respondents. The types of data collected are primary and secondary data. The data that was collected was analyzed using the SWOT analysis method. The research results show that the characteristics of this Moringa chocolate product arethat it is made from selected ingredients combined with Moringa leaves to produce chocolate with a unique, delicious taste and with the addition of cashew nuts and a thick texture. It is not made with preservatives or any chemicals so it is very good for the body with a net weight of 30g for Rp. 10,000/packaging and also includes a production permit number 204530301004-24 along with halal labeling on the packaging. The company's marketing strategy is implemented using a Growth Oriented Strategy. This is because the SWOT analysis Cartesian diagram shows that the highest total score is in the first quadrant where this quadrant is a profitable situation. The Alfa Omega Foundation has many opportunities and strengths so that it can seize and exploit existing opportunities while minimizing weaknesses and overcoming various threats. The Moringa chocolate production process includes preparing raw materials, melting the chocolate, adding Moringa leaf powder, molding the Moringa chocolate, adding condiments, freezing the Moringa chocolate, packaging and labeling, and marketing.